Kupferkomplexe von Bisamiden, V: Anlagerung einzähniger Liganden an binukleare Koordinationsverbindungen - A. Zuberbühler; Th. Kaden (CHIMIA)
N,N'-Bis-(dimethylaminoethyl)-oxamide forms binuclear copper(II) complexes, which can bind one or two monodentate ligands such as imidazole, pyridine, SCN-, CN- and SO32-. The stability constants of the mixed complexes with imidazole were determined by displacement reactions and calculated with a digital computer. All binuclear compounds show a typical UV-absorption band, which probably arises from the transition of an electron from one copper to the other through a π-electron bridge.